Malik Bennabi’s Inspiration to Mahathir Mohammad in Transforming Malaysia’s Development - Fatima SAYAH; Khairunnisa MUSARI (Journal of North African Economies, 2025)
The Malaysian experience in development is considered one of the most successful experiences of that is characterized by its specificity and importance for the third world countries, which can be followed in its footsteps to get rid of underdevelopment and economic dependence. Malaysia has risen and made a qualitative leap in its economy in the economic field during the past four decades thanks to education and adopted the renaissance ideas of Malik Bennabi, who focused on the human being and based his theory on morals, education and teaching. This is in line with the lessons learned in developed countries which focus on investment in human resource development.